2011
DOI: 10.1016/j.ejcts.2011.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors for primary graft failure requiring temporary extra-corporeal membrane oxygenation support after cardiac transplantation in adults☆

Abstract: Occurrence of PGF is a multifactorial event that depends on both donor and recipient profiles. ECMO support is a reliable treatment for severe PGF; furthermore, surviving patients treated with ECMO have the same 1-year conditional survival rates as patients not having suffered a PGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 19 publications
7
86
2
3
Order By: Relevance
“…As previously mentioned, there has been a marked variation in the reported incidence of PGD among studies from individual centres, ranging from 2 % to 26 % [3][4][5]6•, 7-10, 11•], largely due to inconsistencies in the definition for PGD used by different authors. In a large retrospective study of the United Network of Organ Sharing (UNOS) database, Russo et al reported the incidence of PGF at 2.5 % [10]; however, the authors defined PGF as postoperative death or retransplantation within the first 90 days of transplant, indicating that only the most severe cases were included in the analysis.…”
Section: Incidencementioning
confidence: 91%
See 1 more Smart Citation
“…As previously mentioned, there has been a marked variation in the reported incidence of PGD among studies from individual centres, ranging from 2 % to 26 % [3][4][5]6•, 7-10, 11•], largely due to inconsistencies in the definition for PGD used by different authors. In a large retrospective study of the United Network of Organ Sharing (UNOS) database, Russo et al reported the incidence of PGF at 2.5 % [10]; however, the authors defined PGF as postoperative death or retransplantation within the first 90 days of transplant, indicating that only the most severe cases were included in the analysis.…”
Section: Incidencementioning
confidence: 91%
“…The reported incidence and outcomes of PGD have varied markedly among individual centres [3][4][5]6•, 7-10, 11•]. Some of this variability may reflect real differences (possibly reflecting different policies regarding donor and recipient acceptance criteria), but a more likely explanation for the inter-institutional variability is the use of different diagnostic criteria for PGD among centres.…”
Section: Introductionmentioning
confidence: 99%
“…Within the first year, the early phase after transplantation is associated with the highest risk of death. In their article, D'Allesandro and colleagues have analyzed incidence, risk factors, and outcomes of primary graft failure after cardiac transplantation [1]. The authors have to be congratulated for writing an honest and very detailed analysis about their data.…”
Section: Introductionmentioning
confidence: 98%
“…From a consensus conference at the 33rd Annual International Society of Heart and Lung Transplant (ISHLT) meeting, PGD was defined as heart failure without secondary reasons developing within 24 h after HTx [3]. PGD is the major cause of early death after HTx, and there have been many reports about risk factors for the development of PGD, including donor age [4], recipient age [5], ischemic time of donor heart [6], female donor [7], donor-to-recipient weight mismatch [8], small donor heart [9], and so on. Therefore using marginal donors could be related to increased risk of PGD.…”
Section: Introductionmentioning
confidence: 99%